+0  
 
-1
283
2
avatar+280 

My answer was wrong. I started the problem off by conjugate rule, but i think i mesed up somewhere with the lone values near the radical roots. And i was plugging in 0 at the end. Maybe that was wrong.

Veteran  Apr 14, 2017
 #1
avatar
+2

Find the following limit:
lim_(x->0) (sqrt(4 x + 16) - 4)/(7 x)

(sqrt(4 x + 16) - 4)/(7 x) = (sqrt(4 x + 16) - 4)/(7 x):
lim_(x->0) (sqrt(4 x + 16) - 4)/(7 x)

lim_(x->0) (sqrt(4 x + 16) - 4)/(7 x) = 1/7 (lim_(x->0) (sqrt(4 x + 16) - 4)/x):
1/7 lim_(x->0) (sqrt(4 x + 16) - 4)/x

(sqrt(4 x + 16) - 4)/x = ((sqrt(4 x + 16) - 4) (4 + sqrt(4 x + 16)))/(x (4 + sqrt(4 x + 16))) = 4/(4 + sqrt(4 x + 16)):
(lim_(x->0) 4/(4 + sqrt(4 x + 16)))/(7)

lim_(x->0) 4/(4 + sqrt(4 x + 16)) = 4/(4 + sqrt(16 + 4 0)) = 1/2:
1/71/2

1/(2 7) = 1/14:
Answer: | 1/14

Guest Apr 14, 2017
 #2
avatar
+2

Other guest is correct ,limit is 1/14, but use L'Hopital's Theorem.  Much easier.

Limit becomes {1/2(4x+16)^(-1/2)   X   4}/7      (chain rule )

 

= { 2(4x+16)^(-1/2)} /7        now let x tend to zero 

= {2 (1/4)}  /7     = (1/2)  / 7      =     1/14

Guest Apr 14, 2017

26 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.